Aplikasi Sistem Notifikasi Troubleshooting Jaringan (Sintar) Berbasis Web - Akhyar Lubis; Iskandar; Rio Septian Hardinata (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
Troubleshooting is a systematic process of identifying the source of a problem in order to find a solution. The troubleshooting approach is carried out to systematically identify the source of the problem, and network administrators will follow up on reports or complaints from service users. This research aims to quickly identify network issues with devices experiencing disruptions. The solution is to develop a web-based application to monitor network devices. This research is implemented by querying the host table with conditions of "down" or "up," and the results are presented on the dashboard page. Monitoring is carried out based on the building zones in Building A, Building M, and Building I. The ping method is used to check the status of host devices through the Cacti server on the Raspberry Pi web server to detect network issues. The web-based Network Troubleshooting Notification System application can assist administrators in registering devices and monitoring them online, allowing them to monitor the number of devices experiencing "up" or "down" conditions.